Solar charging system for bluetooth solar grass trimmer - Amir Firdaus, Basirun (2019)
Bluetooth Solar Grass Trimmer is a trimmer machine which can be controlled via RC Bluetooth through the smartphones and powered by the solar charging system. It provides a full command to control the moving direction of the trimmer that makes it easy to send start, stop and park commands. Additionally, a systematic photovoltaic (PV) solar system was built in together with the trimmer as the source of electricity to charge the batteries. The fabricating of Bluetooth Solar Grass Trimmer machine is primarily to reduce the electricity consumption and human workforce. Generally, energy storage that used in photovoltaic system application is lead acid battery and knowledge in battery state of charge (SOC) is important in effecting control and energy management. The objective in this project is to install the stand-alone of photovoltaic system as the battery charging system and estimating the battery state of charge based on the voltage value with variation on solar radiation. However, it is difficult to estimate the charging voltage with the variation in solar radiation and operating time of the trimmer as well as battery voltage state when a system of solar charging batteries was added. Therefore, the analysis was conduct and validate by using two estimation methods. The first method used is to determine the battery charging and discharging voltage at constant average solar radiation for 1 hour operating time. Then, the second method used to determine the battery state of charge (SOC) is by calculating the initial and final battery voltage by using interpolation method. The highest charging voltage obtained of the battery by using 30Watt solar module with no load condition was 12.23V, while the highest charging battery voltage with load connection was 11.66V respectively.